Corrigendum: Around $\boldsymbol{\ell }$-independence. (29th June 2020) - Chiarellotto, Bruno; Lazda, Christopher
Abstract : We correct the proof of the main $\ell$ -independence result of the above-mentioned paper by showing that for any smooth and proper variety over an equicharacteristic local field, there exists a globally defined such variety with the same ( $p$ -adic and $\ell$ -adic) cohomology.